2018
DOI: 10.1016/j.optcom.2017.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Highly birefringent elliptical core photonic crystal fiber for terahertz application

Abstract:  Authors can share their preprint anywhere at any time.  If accepted for publication, we encourage authors to link from the preprint to their formal publication via its Digital Object Identifier (DOI). Millions of researchers have access to the formal publications on ScienceDirect, and so links will help your users to find, access, cite, and use the best available version.  Authors can update their preprints on arXiv or RePEc with their accepted manuscript .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(33 citation statements)
references
References 39 publications
0
33
0
Order By: Relevance
“…Also, a near-zero ultra-flattened dispersion value of −0.01 ± 0.02 ps/THz/cm for the y-polarized mode and 0.2 ± 0.05 ps/THz/cm for the x-polarized mode can be obtained in the whole interesting frequency range from 1.1 to 2.0 THz for P = 30%. Compared to the reported THz-PCF in the literature [35][36][37][38][39][40][41][42][43][44][45][46][50][51][52][53], the proposed THz-PCF presents a near-zero ultra-flat dispersion over the widest frequency range of 1.1-2.0 THz with two zerodispersion points (1.06 THz and 1.74 THz). So D core = 378 µm and porosity = 30% is selected as optimal design parameters.…”
Section: Simulation Results and Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Also, a near-zero ultra-flattened dispersion value of −0.01 ± 0.02 ps/THz/cm for the y-polarized mode and 0.2 ± 0.05 ps/THz/cm for the x-polarized mode can be obtained in the whole interesting frequency range from 1.1 to 2.0 THz for P = 30%. Compared to the reported THz-PCF in the literature [35][36][37][38][39][40][41][42][43][44][45][46][50][51][52][53], the proposed THz-PCF presents a near-zero ultra-flat dispersion over the widest frequency range of 1.1-2.0 THz with two zerodispersion points (1.06 THz and 1.74 THz). So D core = 378 µm and porosity = 30% is selected as optimal design parameters.…”
Section: Simulation Results and Discussionmentioning
confidence: 73%
“…More recently, Islam M. S. et al proposed a high birefringence of 6.3 × 10 −2 and flattened dispersion PCF based on Zeonex [43]. K. Paul and K. Ahmed suggested a highly birefringent ultra-low material loss PCF based on TOPAS, which have a birefringence of 1.34 × 10 −2 and a low material loss of 0.053 cm −1 at a frequency of 1THz [44]. Jakeya Sultana et al reported an ultra-high birefringence of 0.086 and an ultra-flattened near zero dispersion of 0.53 ± 0.07 ps/THz/cm in a broad frequency range in 2018 [45].…”
Section: Introductionmentioning
confidence: 99%
“…Some of the enabling technologies available for the fabrication of PCFs include capillary stack and draw [47], drilling [48], extrusion [49], and sol-gel casting [50]. However, capillary stack and draw, drilling, and sol-gel casting are only suitable for fabricating geometries with circular air holes [15]. Extrusion techniques, on the other hand, can be used to fabricate asymmetrical geometries.…”
Section: Fabrication and Practical Feasibilitymentioning
confidence: 99%
“…In 2018, Islam et al introduced nine elliptical air holes in the core to achieve a birefringence of 0.086 and EML of 0.065 cm −1 , but crucial parameters that give insights into the modal propagation characteristics, such as the power fraction, effective area, and total loss, were not reported [14]. The same group [15] proposed a rectangular cladded fiber comprising five elliptical core air holes with a birefringence of 0.063 and EML of 0.06 cm −1 . In 2019, Paul et al proposed a hexahedron-core PC-PCF with a numerical aperture (NA) of 0.52 and EML of 0.066 cm −1 .…”
Section: Introductionmentioning
confidence: 99%
“…Habib M A et al [20] proposed a PCF with a rectangular porous core that can obtain an EML of 0.07 cm −1 and birefringence on the order of 10 -2 . Sultana J et al [21] proposed a PCF with elliptical pores in the core, whose birefringence can be as high as 0.063 at 1 THz. However, the chromatic dispersion of the structure mentioned in [20,21] is relatively high.…”
Section: Introductionmentioning
confidence: 99%